Comparison of Weighted Moving Average and Single Exponential Smoothing Forecasting on Manila Duck Eggs Production - Gusman Simon (JOMLAI: Journal of Machine Learning and Artificial Intelligence, 2026)
As a waterfowl, the Manila duck is a potential livestock option and a source of animal protein for the community. Its population growth is still considered low, and its egg production capacity only serves to support the food supply. Population growth and public awareness of the importance of nutrition drive the demand for animal protein consumption. The highest growth in duck egg consumption was observed between 2014 and 2018. In 2021 and 2022, the production and consumption of Manila duck eggs increased per capita every week. However, in 2024, the production rate of Manila duck eggs decreased. One way to anticipate the risk of declining Manila duck egg production is through predictive analysis. Based on the data patterns obtained from the Central Statistics Agency, the weighted moving average (WMA) forecasting method and single exponential smoothing (SES) were selected. The MAPE value of the WMA method for the last two periods 6.742%, last three periods 6.444%, and last four periods 6.814%. The MAPE value of the SES method is 6.466%. The lowest MAPE value is from the 3-period WMA method. To minimize the MAPE value, the Solver add-in application attached in MS Excel is used to determine the weight value of each period in the WMA method, as well as the smoothing coefficient value of the SES method.